PENGUKURAN KUALITAS USABILITY PADA APLIKASI SISTEM KEUANGAN DESA MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Kevin Vera Pedjaga; Agus Lahinta; Dian Novian (Diffusion: Journal of Systems and Information Technology, 2021)
Most people have used information technology to reach certain goals. Pagimana District is one of the region in Banggai Regency that has utilized the development of information technology to ease the work of the government. The Village Financial System ( henceforth, SISKEUDES) functions to facilitate the village government in managing, implementation and reporting village funds. Therefore, i tis essential to measure the quality and amenity of SISKEUDES usage for users by evaluating some aspects, i.e., intelligibility, user-friendliness, and efficiency in terms of facilitating the village government's work. This present study relied on the System Usability Scale (SUS) method by distributing a questionnaire to respondents. It shows the usability grade in the SISKEUDES app (57, poor category), in which users find it unsatisfactory to apply the system. This can be a benchmark for the central government to better the system develompment that meets the user's needs.